Influence of hybrid nano Al2O3–ZrO2 reinforcements on microstructure, fracture toughness and fractographic behaviour of Al6061 alloy (Fracture and Structural Integrity, 2026)
A present study reveals the influence of nano Al2O3 and ZrO2 reinforcements on the fracture toughness of Hybrid Metal matrix Composites (HMMCs) made of Al6061 alloy. Composites are synthesized by varying weight fraction of alumina and Zirconia oxide using ultrasonic stir casing technique. Microstructural characterization of the synthesized composites for different weight fractions are carried out by using Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS) and X-ray Diffraction (XRD) which shows the uniform dissemination of the reinforced particulates, elemental composition and formation of phases. As per ASTM E399 fracture toughness was investigated which indicates the addition of nano sized reinforced particulates into the matrix alloy enhances the crack propagation resistance. Among the produced nano composites, Al6061-1 wt. % of Al2O3p+ ZrO2p shows maximum fracture toughness (47.39%) due to uniform dissemination of the nano reinforced particulates and load bearing capacity. The fractographic examination revealed a transition from ductile to mixed-mode fracture, with nanoparticles adequately disseminated to impede crack propagation and improve energy absorption. Meanwhile, further increase in the weight fraction of the reinforcing particulates leads to agglomeration there by reduces the fracture toughness. The results show that optimized nano hybrid reinforcement improves fracture toughness of Al6061 alloy and making it suitable for structural applications.
Keywords: Al6061; Stir casting; Nano- Al2O3, ZrO2; SEM; Fracture Toughness